Patients with chronic lymphocytic leukemia with high-risk genomic features have inferior outcome on successive Cancer and Leukemia Group B trials with alemtuzumab consolidation: subgroup analysis from CALGB 19901 and CALGB 10101. Issue 12 (December 2013) - Jones, Jeffrey A.; Ruppert, Amy S.; Zhao, Weiqiang; Lin, Thomas S.; Rai, Kanti; Peterson, Bercedis; Larson, Richard A.; Marcucci, Guido; Heerema, Nyla A.; Byrd, John C.
Abstract Alemtuzumab consolidation has been investigated to improve remission duration after fludarabine-based induction for chronic lymphocytic leukemia (CLL). The impact on genomic high-risk disease remains unknown. Cancer and Leukemia Group B (CALGB) 19901 and 10101 enrolled previously untreated patients to receive alemtuzumab consolidation after fludarabine-based induction. Immunoglobulin heavy chain gene (IGVH) mutation status and interphase cytogenetics were assessed retrospectively. Treatment response with these alemtuzumab-containing regimens was similar, regardless of genomic risk, except for patients harboring del(17p), where few complete remissions were observed. Progression-free survival (PFS) was similar between IGVH groups, but overall survival (OS) was inferior in IGVH unmutated patients (p = 0.03). Cytogenetic risk group was associated with PFS and OS (p = 0.01 for both), with similarly short PFS in patients with del(17p) and del(11q) and particularly short OS in patients with del(17p). Cytogenetic risk group remained signficantly associated with PFS and OS when controlling for other prognostic factors (PFS: p = 0.009; OS: p = 0.02), as did the negative association of IGVH unmutated disease with OS (p = 0.004). Results were similar when restricting to patients who received at least one dose of alemtuzumab consolidation, demonstrating limited ability to overcome the poor outcome associated with high-risk genetic features (ClinicalTrials.gov identifiers: NCT00004857, NCT00098670).